2012
DOI: 10.1021/mp200673n
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Procaspase-3 Activating Compounds in the Induction of Cancer Cell Death

Abstract: The evasion of apoptosis is a key characteristic of cancer, and thus strategies to selectively induce apoptosis in cancer cells hold considerable promise in personalized anticancer therapy. Structurally similar procaspase activating compounds PAC-1 and S-PAC-1 restore procaspase-3 activity through the chelation of inhibitory zinc ions in vitro, induce apoptotic death of cancer cells in culture, and reduce tumor burden in vivo. IP or IV administrations of high doses of PAC-1 are transiently neurotoxic in vivo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 62 publications
2
45
0
Order By: Relevance
“…In addition, we have also shown that PAC-1 significantly enhances the antitumor activity of paclitaxel, both in vitro and in NSCLC xenograft model. Our data on NSCLC complement previous studies on proapoptotic effects of PAC-1 in different cancers [20]. The proapoptotic effects of PAC-1 are proportional to the cellular levels of PC-3.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, we have also shown that PAC-1 significantly enhances the antitumor activity of paclitaxel, both in vitro and in NSCLC xenograft model. Our data on NSCLC complement previous studies on proapoptotic effects of PAC-1 in different cancers [20]. The proapoptotic effects of PAC-1 are proportional to the cellular levels of PC-3.…”
Section: Discussionsupporting
confidence: 87%
“…65 The mechanism of action of PAC-1 most likely involves the chelation of labile zinc from procaspase-3, relieving the zinc-mediated inhibition and allowing procaspase-3 to process itself to the active form. 36, 37, 41 Using genetically-encoded zinc sensors, PAC-1 has been shown to mobilize the labile zinc pool in cancer cells. 41 Providing further support to this direct procaspase-3 activation mechanism, cells treated with PAC-1 or a derivative show cleaved procaspase-3 and poly-ADP ribose polymerase-1 prior to release of cytochrome c from the mitochondria or cleavage of initiator procaspases-8 and -9, 8, 42, 43, 66 and PAC-1 -mediated apoptosis occurs regardless of the status of Bcl-2 family proteins.…”
Section: Introductionmentioning
confidence: 99%
“…36, 37, 41 Using genetically-encoded zinc sensors, PAC-1 has been shown to mobilize the labile zinc pool in cancer cells. 41 Providing further support to this direct procaspase-3 activation mechanism, cells treated with PAC-1 or a derivative show cleaved procaspase-3 and poly-ADP ribose polymerase-1 prior to release of cytochrome c from the mitochondria or cleavage of initiator procaspases-8 and -9, 8, 42, 43, 66 and PAC-1 -mediated apoptosis occurs regardless of the status of Bcl-2 family proteins. 67, 68 Because of this unique mechanism, PAC-1 is increasingly being used as a tool to directly activate procaspase-3 in a variety of biological settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previous studies showing that zinc inhibits caspase-3 with an IC 50 of 0.1 μ M (Perry et al, 1997). They also reported that the zinc-chelation mechanism was responsible for the cell death observed in cell culture leading to altered intracellular Ca 2+ concentration, indicative of endoplasmic reticulum stress-induced apoptosis (West et al, 2012). In summary, PAC-1 may not be a direct activator of procaspase, but led to interesting discoveries about the role of metal chelation in caspase activation and initiation of cell death.…”
Section: Small-molecule Activators Of Caspasesmentioning
confidence: 99%